Enhanced breakdown strength of aligned-sodium-titanate- nanowire/epoxy nanocomposites and their anisotropic dielectric properties. (May 2019) - Chen, Siyu; Cheng, Yonghong; Xie, Qian; Xiao, Bing; Wang, Zhengdong; Liu, Jingya; Wu, Guanglei
Abstract: In this work, sodium titanate (Na2 Ti6 O13 ) nanowire/epoxy nanocomposites with different nanowire alignments and thicknesses were fabricated by employing the DC electric field during curing process. Nanocomposites showed obvious anisotropic dielectric properties. When nanowires were aligned perpendicularly to the electric field directions (X-Y-aligned), the breakdown strength (EB ) of nanocomposites with thickness of 1 mm and 0.5 wt% nanowires increased by 9.6% or 11%, compared to that of pure epoxy or no-alignment nanocomposites. When the thickness decreases to 10 μm, the EB enhancement further increased to 87%, compared to that of no-alignment samples. Thermally stimulated discharge current (TSDC) results indicated that more electronic deep traps were introduced perpendicular to alignment direction of nanowires and more shallow traps existed in the direction parallel to the oriented nanowires. The origin of the anisotropy in EB of nanocomposites was studied by analyzing the orientations of interfaces and the nanowires' anisotropic crystal structure. This work gives invaluable guidelines for designing of thermoset functional materials.